PENGARUH AGENCY COST, RETURN ON EQUITY (ROE), DAN FREE CASH FLOW TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2010-2019 - Sarah Hasibuan, Siti; Hakim, Lukmanul (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
The dividend of a company is always a concern for shareholders to invest. Information regarding the state of the company can be seen in the financial statements. This study aims to examine the effect of Managerial Ownership, Return On Equity and Free Cash Flow on the Dividend Payout Ratio in manufacturing companies listed on the Indonesia Stock Exchange for the 2010-2019 period. According to Sartono, dividends are profits obtained by the company and distributed to shareholders. Decisions regarding the amount of dividends will be determined at the General Meeting of Shareholders (GMS). The results of this study indicate that Managerial Ownership has a positive and significant effect on the Dividend Payout Ratio. Return On Equity has a negative and insignificant effect on the Dividend Payout Ratio and Free Cash Flow has a positive and insignificant effect on the Dividend Payout Ratio.